On the nature of the Ni-rich component in splash-form Australasian tektites. (15th November 2017) - Goderis, Steven; Tagle, Roald; Fritz, Jörg; Bartoschewitz, Rainer; Artemieva, Natalia
Abstract: The Australasian tektite strewn field is exceptional, not only as the largest and most recent, but also as the only strewn field without an identified source impact crater. Therefore, scenarios without the formation of an impact crater, such as a low altitude cometary airburst, have proven hard to discard. Here, new geochemical evidence is presented for mixing of projectile and target material, which implies the formation of an Australasian tektite-related impact crater. First, ninety-two Australasian tektites were grouped according to their Cr, Co and Ni concentrations. Based on this data, Australasian tektites with the highest Ni contents (>200 μg/g) occur more than 1500 km south-southeast (SSE) of the northern Indochina region, with the highest concentration of Ni-rich tektites in South Vietnam, the islands of Borneo, Belitung, and Java, and reports in literature for Ni-rich tektites in central Australia. The tektites with the highest Cr and Ni abundances often also show highly siderophile element (HSE) enrichments of up to 4 ng/g Ir. The most Ni-rich samples exhibit broadly chondrite-relative HSE proportions. However, a chondritic impactor contribution appears to be inconsistent with the observed Ni/Cr, Ni/Co, and Cr/Co ratios. A previously suggested significant terrestrial mantle contribution can also not explain the siderophile element enrichments in combination with relatively low FeOtot (<7 wt.%) and MgO (<4 wt.%) contents. Elemental fractionation during impact cratering or tektite formation by an impactor with a chondritic signature may explain these observations. Alternatively, a projectile component from a primitive achondrite may be advocated, with contribution from a mafic to ultramafic extraterrestrial lithology with a relatively unfractionated HSE signature and Ni/Cr ratio distinctly higher than those of Earth's mantle. Element distribution maps obtained from individual Australasian tektites document complex mingling processes of chemically distinct melt batches, each exhibiting variable contributions from distinct endmember compositions. These texturally recorded mingling processes are consistent with high-resolution numerical models of impact cratering processes that resolve the growth of Kelvin-Helmholtz instabilities at the projectile/target interface during impact, when both materials co-occur at high pressure. These numerical models indicate that Ni-rich tektite populations across the central part of the Australasian tektite strewn field could represent projectile-enriched material preferentially ejected downrange. Continued tracing of this Ni-rich component across the strewn field may help to constrain the location of the yet to be identified source crater of the Australasian (micro)tektites.